IMPACT OF MYCOFLORA ON RICE QUALITY AND STORAGE IN MADHUBANI DISTRICT - Kumari, Sanju; Kumar, Amar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Bioassays provide a reliable method for evaluating air quality through the examination of different bioparticles, including their occurrence, absence, quantity, distribution, shape, and biochemical properties. Bioparticles, including pollen, spores, bacteria, and other microbes, are crucial indicators of environmental conditions. These particles elicit responses from sensitive species of plants and animals, as well as humans, which offer valuable insights about air quality. Researchers can assess the environmental health of specific places by accurately measuring and establishing the habitat reactions and sensitivity of biological species. Within this context, there is a special emphasis on fungal spores due to their crucial role as environmental bioparticles that have well-documented effects on health. These spores are widely recognized for their capacity to induce dermatological, pulmonary, and cardiac ailments, as well as allergy symptoms in humans. Fungal spores have negative impacts not just on human health but also on other species and ecosystems. In order to investigate these concerns, an initial investigation was carried out on the presence of airborne fungi in rice mills situated in Madhubani. Rice mills provide an environment conducive to the growth and spread of fungi due to the processing of vast amounts of organic waste. The objective of this study was to categorize the many types of fungal spores found, measure their abundance in the atmosphere, and analyze their possible effects on both the mill workers and the neighboring population. The findings offer useful insights into the management of air quality and contribute to the development of methods to reduce the health concerns linked to exposure to airborne fungus spores.